Design and numerical simulation of direct cooling evaporators for chip thermal test based on triply periodic minimal surfaces - Feng Guo; Jiahong Fu; Yi Zhao; Xing Huang; Zhongyao Tong; Junqi Bao; Xiaoge Duan; Yuanxu Feng; Bengt Sunden (Case Studies in Thermal Engineering)
Aiming at the three-temperature test requirements of high-power density chips, the third generation of refrigerant direct cooling technology has been developed. Three kinds of direct cooling evaporators with triply periodic minimal surfaces (TPMS) are designed and systematically simulated in this paper. The mechanism of augmentation of heat transfer are determined, and the thermal characteristics of the direct cooling evaporators of TPMS are analyzed. The results indicate that the Primitive relies on faster fluid flow and the formation of eddy currents to enhance heat transfer. However, due to the large resistance, the comprehensive performance of the Primitive is 70–78 % worse than that of a conventional serpentine channel, while the flow resistance of Diamond and Gyroid is smaller, and the comprehensive performance is 432–845 % and 238–450 % better than that of a serpentine channel, respectively. The validity of the phase change simulation method is verified by comparing the results of the phase change simulation of a copper tube with experimental results, with a maximum error of 4.9 %. The Diamond channel with the best comprehensive performance is considered and numerically simulated by this method, and heat flux distribution and temperature field close to the actual values are obtained.